Evaluation of the Growth and Yield of Organic Corn Fodder under Various Watering Times and Concentrations of Rabbit Urine Fertilizers - Okti Widayati; Bangkit Lutfiaji Syaefullah; Sritiasni Sritiasni; Nani Zurahmah; Aswandi Aswandi; Irma Irma (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
Organic Fodder System is a planting system without using soil as its main medium. The use of fertilizers can be regulated in quantities and concentrations that correspond to the needs of plants during the plant growth season to obtain optimal results with good quality. The study was conducted to determine corn fodder's growth productivity and nutrient content under the treatment of differences in watering time and rabbit urine fertilizer concentration. The treatment was carried out on the difference in the soaking solution of corn kernels and the difference in the watering time of corn seedlings. Soaking was carried out by 5 solutions namely L0: water, L1: AB mix (commercial fertilizer) 1%, L2: rabbit urine fertilizer 1%, L3: rabbit urine fertilizer 2.5%, L4: rabbit urine fertilizer 5%, as treatment, and 5 (five) replication groups. Watering was carried out at three different time intervals (W1: 6 hours/day, W2: 9 hours/day, W3: 12 hours/day) with five replication groups. The variables observed were germination percentage, normal sprout percentage, corn fodder height, fresh fodder production, fodder dry matter production, fodder protein content, fodder crude fiber content, fodder crude fat content, Non-Nitrogen Free Extract (NNFE), and corn fodder ash content. The experimental design used in this study was a Completely Randomized Design of factorial patterns. Differences in rabbit urine fertilizer concentration and watering time impact germination percentage, normal germination percentage, plant height, fresh matter production, dry matter production, protein content, and crude fiber.